PENERAPAN PEMBELAJARAN MATEMATIKA MODEL ELABORASI DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SUB POKOK BAHASAN JAJAR GENJANG DAN BELAH KETUPAT SISWA KELAS VIIB SEMESTER GENAP DI SMP NEGERI 1 JATIBANTENG TAHUN AJARAN 2012/2013 - Indrayani, Lilik; Susanto, S; Suharto, S (Department of Mathematics Education , University of Jember, 2014)
Abstract. Generally, mathematics learning in the school still concentrates on the teachers, so that the students become passive in the learning process. Besides that, the students also never get a problem which is done as a group work. This matter cause the students become passive and only listen about the teacher’s explanation. That matter also makes the students become bored, get difficulties in studying Mathematics and give impact on the student’s bad result. Because of that, a resolution is needed to make a better learning process by applying the elaboration learning method on parallelogram and rhombus chapter to increase the study result of the students of VIIB class in SMP Negeri 1 Jatibantengacademic year 2012/2013. Elaboration method is started from presentation of epitome or a framework of that contains and the last is giving the conclusion which has a function to combine some concepts. Based on the result of the research, the application of elaboration learning method is effective to increase the study result of the students in parallelogram and rhombus chapter. We can see it from the student’s study result, that is from 55% to 87.5%. Key Words:Elaboration model, students’ activity, student learning achievement